Comparative study of open mesh repair and Desarda’s no-mesh repair for inguinal hernia, in GMKMCH, Salem, India - ., Prakash; Mohan, Padmalakshmi Bharathi (International Surgery Journal, 2018)
Background: Mesh repair has gained popularity among the surgical repair of hernias but has limitations. This study is being carried out to compare the effectiveness of Desarda’s no mesh repair, with Lichtenstein’s tension free repair. Methods: This prospective study was carried out in GMKMCH, Salem, over a period of 2 years. A total of 60 cases with inguinal hernia were included in the study. 30 patients were randomly subjected to Desarda’s technique and 30 patients underwent Lichtenstein’s repair. After surgery, patients were followed up and noted for complications like groin pain, surgical site infections, duration of hospital stay, duration to return to normal activity. Results: Operative time was 45 minutes in Desarda’s group and 50 minutes in the Lichtenstein group which was highly significant (p<0.01). On 2-year follow-up there were no recurrences in both groups. There were no surgical site infections in the Desarda’s group, compared to whereas Lichtenstein’s repair where had 4 (10%) recurrences. The occurrence of complications like loss of sensation over the groin, scrotal edema, abdominal wall stiffness was not seen in Desarda’s group, whereas its occurrence was highly significant (p<.01) in Lichtenstein’s group. Conclusions: Desarda’s no mesh technique is easy to learn and simple when compared to other no mesh repair techniques and requires no mesh. It can be used in a contaminated surgical field, in young individuals and in cases of financial constraints. Hence, Desarda’s no mesh repair is favourably comparable with Lichtenstein’s mesh repair.